2020
DOI: 10.5114/aoms.2019.86969
|View full text |Cite
|
Sign up to set email alerts
|

Klotho and vitamin D in multiple sclerosis: an Italian study

Abstract: Introduction: Low vitamin D levels have been recognised as an important risk factor for autoimmune diseases, including multiple sclerosis (MS). MS is a multifactorial disease, the pathogenesis of which contributes both to genetic and environmental factors. Polymorphisms in genes codifying molecules involved in vitamin D homeostasis have been associated with hypovitaminosis D. However, the influence of polymorphisms of Klotho, which codify a protein with a pivotal role in vitamin D metabolism, have never been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
1
10
0
1
Order By: Relevance
“…Insulin resistance status was assessed as homeostasis model assessment of insulin resistance (HOMA Index) according to the following formula: [insulin (μU/mL)* glycaemia (mg/dL)]/405. Vitamin D was evaluated as previously described [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Insulin resistance status was assessed as homeostasis model assessment of insulin resistance (HOMA Index) according to the following formula: [insulin (μU/mL)* glycaemia (mg/dL)]/405. Vitamin D was evaluated as previously described [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The genes that encode the enzymes involved in the vitamin D pathway are highly polymorphic [27]. These genetic alterations may influence the expression of those genes in lung tumor tissue, modifying the activity of vitamin D [15,28,36,[38][39][40][41]. Therefore, they may play a vital part in the development, progression, and prognosis of NSCLC [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that Klotho in the brain of AD patients and mouse models was significantly lower than in age‐matched healthy groups (Dubal et al, 2015; Kuang et al, 2017; Massó et al, 2015; Semba et al, 2014). More researches have provided indications that Klotho may alleviate an array of neurodegenerative diseases (Jamali‐Raeufy et al, 2017; Dubal et al, 2015; Scazzone et al, 2019; Zeldich et al, 2019). These findings provide convincing evidence that Klotho may be a novel therapeutic target for the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%